"Identificación de la concentración mínima inhibitoria (CMI) de los aceites esenciales Cymbopogon ciratus (hierba luisa) y Ziingiber officinale (jengibre) en hongos adheridos a la Annona muricata L.(guanábana) para prolongar su vida útil" - Zamora Rodiguez, Verónica Liseth (2017)
This research aims to identify the minimum inhibitory concentration (MIC) of the essential oils Cymbopogon ciratus (herb luisa) and Zingiber officinale (ginger) in fungi attached to Annona muricata L., (guanabana) to prolong its shelf life, that is why it is investigation a proposal that will allow to evaluate the antifungal activity of the essential oils Cymbopogon ciratus (herb luisa) and Zingiber officinale (ginger) in three levels of concentration (10, 15, 20%) against the fungi Macrophoma sp., Verticillum sp., microorganisms that cause deterioration in post-harvest, a completely randomized block design was applied with a factorial arrangement AxBxC that consisted of 12 treatments and 2 replications, which corresponds to 24 treatments. The study factors were: Factor A (fungi), factor B (essential oils) and factor C (concentrations). To establish the differences between the levels, Tukey significance tests were applied (p <0.05), using the statistical program StatGraphics and Infostat. The fungi were isolated and identified from Annona muricata L. (guanábana), was performed with the technique of Papa Dextrose Agar (PDA) plus essential oil solution and tween 20 for a homogeneous mixture in which mycelial growth was evaluated and the percentage (%) of inhibition in 24, 72, 120 hours. To identify the minimum inhibitory concentration of essential oils, the concentrations of (10, 15, 20%) were evaluated. After comparison with several authors, it was determined that the essential oils that totally inhibit the fungus were determined the minimum inhibitory concentration (MIC). ) since the best treatment was a0b0c2 = T3 (Macrophoma sp + AE Luisa grass + 20%) since it completely inhibited the fungus Macrophoma sp., Physical and chemical analysis was carried out on Annona muricata L., (guanábana) for thus determine its shelf life in which it managed to reach 15 days of preservation while maintaining its appearance. Key Words: Mycelium, Minimum inhibitory concentration, Essential oil, Microorganisms, Radial growth, concentrations